Fundamentals of education research - Anderson, Gary.; Arsenault, Nancy (London : Falmer Press, 1998)
Cuts through the complexities of educational research to give the novice reader a sound basis to define, develop, and conduct study, while providing insights for even the accomplished reader.
Includes index.
Keywords: Education . -- Research; Education -- Research -- Methodology